Nano polyelectrolyte complexes of carboxymethyl dextran and chitosan to improve chitosan-mediated delivery of miR-145. (1st March 2017) - Tekie, Farnaz Sadat Mirzazadeh; Kiani, Melika; Zakerian, Amir; Pilevarian, Faezeh; Assali, Akram; Soleimani, Masoud; Dinarvand, Rassoul; Arefian, Ehsan; Atashi, Amir; Amini, Mohsen; Atyabi, Fatemeh
Highlights: PEC stability and dissociation rate are crucial factors for gene delivery. PEC preparation method affect its characteristics including size distribution. Depending to Ch Mw and CMD:Ch ratio, nano PECs are efficient gene delivery systems. Abstract: Chitosan (Ch) nanoparticles have emerged as a promising vector for gene delivery, nonetheless slow dissociation rate of the nanoparticles in cytoplasm is a drawback of using Ch. Herein, the Ch-mediated gene delivery was improved using PECs of Ch and carboxymethyl dextran (CMD) to transfer the micro RNA-145 (miR-145). The optimized nano PEC preparation method and effects of Ch molecular weight (Mw) and a CMD to Ch molar ratio (CMD:Ch) on physical characteristics and in vitro efficacy of the nano PECs was determined. The size of the nano PECs depended on the preparation method, Ch Mw, and CMD:Ch ratio. Also, the Ch Mw and CMD:Ch affected stability of the miR-145 PECs in presence of heparin. In vitro tests indicated the different gene transfection efficiency of the nano PECs with various compositions. As a novel vector, these nano PECs have excellent promise for gene delivery with an adequate balance between a complex stability and dissociation rate.